Hot-pressed component and method for manufacturing the same

By dispersing and analyzing cementite and Ti-based carbides in the hot pressing member, forming a martensite structure with excellent toughness and a hydrogen capture point, the problem of insufficient delay-resistant fracture characteristics of the hot pressing member in the prior art is solved, and a combination of high strength and high toughness is achieved.

CN116234933BActive Publication Date: 2025-05-02JFE STEEL CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202180055364.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-08-28
Filing Date
2021-06-22
Publication Date
2025-05-02
Estimated Expiration
2041-06-22

AI Technical Summary

Technical Problem

The prior art is difficult to improve the delayed fracture resistance of the hot pressed member while maintaining a tensile strength of 2100 MPa or above. Especially in the automotive assembly process, the hot pressed member still has the risk of delayed fracture after stress is applied.

Method used

By dispersing and abating the cementite in the hot pressing member, the amount of solid solution C in the martensite is reduced and the dislocation density is reduced, forming a martensite structure with excellent toughness, and at the same time, the fine Ti-based carbides are dispersed into the capture point of hydrogen, thereby improving the delay-resistant fracture characteristics.

Benefits of technology

While the tensile strength is 2100 MPa or above, the delay fracture resistance of the hot pressed member is significantly improved, ensuring high strength and toughness of the member in actual use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004113237740000191
    Figure BDA0004113237740000191
  • Figure BDA0004113237740000201
    Figure BDA0004113237740000201
  • Figure BDA0004113237740000211
    Figure BDA0004113237740000211
Patent Text Reader

Abstract

The object of the present invention is to provide a hot pressed component having a tensile strength of 2100 MPa or more and excellent delayed fracture resistance and a method for manufacturing the same. The hot pressed component of the present invention has the specified composition as described in claims 1 and 2, and satisfies 2.0≤Ti / Sb≤20.0, and in the microstructure of the hot pressed component, martensite accounts for more than 95% by volume, and the average crystal grain size of the prior austenite is less than 7 μm, and the cementite with a grain size of 0.10 μm or more is 2 / μm. 2 Above, the Ti-based carbides with a particle size of 0.10 μm or less are 0.20 / μm 2 In addition, the tensile strength of the hot pressed component is 2100 MPa or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a hot-pressed component having both a tensile strength of 2100 MPa or more and excellent delayed fracture resistance and a method for producing the same. Background Art

[0002] In recent years, due to the aggravation of environmental problems, CO2 emission restrictions have become strict, and the lightweighting of the car body for improving fuel efficiency has become a topic in the automotive field. For this reason, thin-walling is being promoted by applying high-strength steel plates in automotive parts, and the application of steel plates with a tensile strength (TS) of more than 2100MPa is being studied. High-strength steel plates used in structural components and reinforcement components of automobiles require excellent formability, but the ductility of steel plates above 2100MPa is low, so cracks are generated during cold forming, or large rebound occurs due to high yield strength, so high dimensional accuracy cannot be obtained after cold forming. In addition, residual stress remains in the steel plate after cold forming, so it is possible to cause delayed fracture (hydrogen embrittlement) due to hydrogen intruding from the use environment.

[0003] Under such circumstances, as a method of obtaining high strength, attention has recently been paid to press forming using hot pressing (also known as hot stamping, die quenching, press quenching, etc.). Hot pressing is a forming method in which a steel plate is heated to a temperature range of austenite single phase, and then formed (processed) at a high temperature, thereby forming with high dimensional accuracy, and quenching is performed by cooling after forming, thereby achieving high strength. In addition, in this hot pressing, the residual stress after press forming is reduced compared to cold pressing, so the delayed fracture resistance is also improved.

[0004] However, in the automobile assembly process, when the hot-pressed components are assembled by resistance spot welding or the like after press forming, stress is applied to the hot-pressed components after hot pressing in order to maintain the rigidity of the entire automobile body, and therefore, the concern about delayed fracture after press forming cannot be eliminated. Therefore, it is necessary to improve the delayed fracture resistance of the hot-pressed components after hot pressing.

[0005] Conventionally, several methods for improving delayed fracture resistance after hot pressing have been reported.

[0006] For example, Patent Document 1 discloses a technique for improving delayed fracture resistance by controlling the precipitation amounts of alloy carbonitrides and cementite.

[0007] In addition, Patent Document 2 discloses a technique for improving delayed fracture resistance by forming retained austenite after hot pressing.

[0008] Prior art literature

[0009] Patent Literature

[0010] Patent Document 1: Japanese Patent No. 6062352

[0011] Patent Document 2: Japanese Patent No. 5942841 Summary of the invention

[0012] Problems to be solved by the invention

[0013] However, it is difficult to improve the delayed fracture resistance in the high-strength region of tensile strength of 2100 MPa or more in the methods of Patent Documents 1 and 2, and the actual situation is that a hot-pressed component having both these characteristics has not yet been developed.

[0014] Therefore, an object of the present invention is to provide a hot-pressed component having both a tensile strength of 2100 MPa or more and excellent delayed fracture resistance, and a method for producing the same.

[0015] Methods used to solve problems

[0016] In view of the above-mentioned actual situation, the inventors of the present invention have repeatedly conducted in-depth studies and found that in order to improve the delayed fracture resistance of hot-pressed components, the cementite is dispersed and precipitated in the component to reduce the amount of dissolved C in martensite and at the same time reduce the dislocation density, thereby making the component structure martensite with excellent toughness. In addition, the delayed fracture resistance is improved by dispersing fine Ti-based carbides to become hydrogen capture points.

[0017] If the hardness of martensite is increased to make the component high-strength, the toughness deteriorates, and when the collision is performed as the actual driving after the automobile body is processed, it is possible to break with a strength lower than the actual component strength. Therefore, it is necessary to improve toughness while ensuring strength. In addition, in the process of actual repeated driving, hydrogen is electrochemically generated on the component due to rain, etc., and a part of it invades the component. At this time, if stress is not generated in the component, delayed fracture will not occur due to the hydrogen, but in order to maintain the rigidity of the entire automobile body, there is also a part of stress applied in the component after hot pressing. The cathode reaction of the corrosion reaction caused by rain, etc. is mainly the reduction reaction of oxygen, but a part is the reduction reaction of hydrogen. Therefore, it is found that by tempering at low temperature after hot pressing, cementite is dispersed and precipitated, and a martensitic property with reduced dislocation density is formed, thereby cementite becomes a hydrogen capture point while toughness is restored, and the delayed fracture resistance is improved. Furthermore, it was found that Ti-based carbides also serve as trapping sites for hydrogen having high activation energy required for hydrogen desorption, thereby suppressing delayed fracture. Therefore, even when the tensile strength is 2100 MPa or more, the delayed fracture resistance is good.

[0018] The present invention is based on the above findings, and the gist of the present invention is as follows.

[0019] [1] A hot pressed component, comprising, in mass%, C: 0.41% to 0.53%, Si: 0.01% to 0.80%, Mn: 1.0% to 2.0%, P: 0.03% to 0.003%, S: 0.003%, Al: 0.01% to 0.10%, N: 0.006% to 0.003%, Nb: 0.003% to 0.018%, Ti: 0.008% to 0.100%, B: 0.0005% to 0.0050%, Sb: 0.003% to 0.015%, the balance being Fe and unavoidable impurities, satisfying 2.0≤Ti / Sb≤20.0,

[0020] The microstructure is as follows: the volume fraction of martensite is 95% or more, the average grain size of the prior austenite is 7 μm or less, and the cementite with a grain size of 0.10 μm or more is 2 / μm. 2 The number of Ti-based carbides with a particle size of 0.10 μm or less is 0.20 / μm. 2 above,

[0021] The tensile strength of the hot-pressed component is greater than 2100 MPa.

[0022] [2] The hot-pressed component as described in [1], wherein the component composition further contains, in terms of mass%, one or more selected from the group consisting of Mo: 0.35% or less, Cr: 0.35% or less, V: 0.05% or less, Ca: 0.005% or less, Cu: 0.50% or less, Ni: 0.50% or less, and Sn: 0.50% or less.

[0023] [3] The hot pressed component according to [1] or [2], wherein the hot pressed component has an Al-based plating layer or a Zn-based plating layer on a surface thereof.

[0024] [4] A method for manufacturing a hot-pressed component, wherein a cold-rolled steel sheet having the composition described in [1] or [2] is heated to a temperature range of not less than the Ac3 transformation point and not more than 1000°C and then hot-pressed, cooled to not more than Ms point - 200°C and then reheated under the conditions of a reheating temperature of not less than 100°C and not more than 220°C and a holding time of not less than 1 minute and not more than 40 minutes.

[0025] Effects of the Invention

[0026] According to the present invention, a hot-pressed component having both a tensile strength of 2100 MPa or more and excellent delayed fracture resistance can be obtained. DETAILED DESCRIPTION

[0027] The present invention will be described in detail below. First, the reasons for limiting the composition of the hot press member of the present invention will be described. In the following, "%" of a component means mass %.

[0028] C: 0.41% or more and 0.53% or less

[0029] C is an element effective in increasing the strength of steel sheets, and is an important element for strengthening martensite after hot pressing to increase the strength of steel. However, when the C content is less than 0.41%, the hardness of the martensite after hot pressing is insufficient, so tensile strength cannot be obtained. It is preferably 0.42% or more. On the other hand, when it exceeds 0.53%, the toughness is extremely reduced, and fracture occurs before the plastic unstable region, so tensile strength cannot be obtained. It is preferably less than 0.52%, and more preferably less than 0.50%.

[0030] Si: 0.01% or more and 0.80% or less

[0031] Si is an element that solid-solution strengthens ferrite and is effective for high strength. However, excessive Si content leads to deterioration of chemical conversion treatment properties, so the content is set to 0.80% or less. Preferably, it is 0.70% or less. In addition, extremely low Si content increases costs, so Si is set to 0.01% or more.

[0032] Mn: 1.0% or more and 2.0% or less

[0033] Mn is an element that improves the hardenability during hot pressing and thus contributes to the formation of martensite after hot pressing, i.e., high strength. In order to obtain this effect, it is necessary to contain 1.0% or more. Preferably, it is 1.2% or more. On the other hand, when it is contained in excessive amounts, excessive Mn bands are generated, thereby generating high-hardness martensite, and cracks are easily generated during hydrogen intrusion, so the delayed fracture resistance is reduced. Therefore, its content is set to 2.0% or less. Preferably, it is 1.8% or less.

[0034] P: 0.03% or less

[0035] P contributes to high strength by solid solution strengthening, but when contained in excess, segregation to the grain boundary becomes significant and the grain boundary becomes embrittled, thereby reducing delayed fracture resistance. Therefore, its content is set to 0.03% or less. Preferably, it is 0.02% or less. Although there is no particular lower limit, extremely low P leads to increased steelmaking costs, so it is preferably contained at 0.0005% or more.

[0036] S: 0.003% or less

[0037] When the S content is high, a large amount of sulfides such as MnS are generated, and the inclusions thereof become starting points for cracking, thereby reducing the delayed fracture resistance. Therefore, the upper limit of the content is set to 0.003%. It is preferably 0.002% or less. Although there is no particular lower limit, extremely low S leads to an increase in steelmaking costs like P, so it is preferably contained at 0.0001% or more.

[0038] Al: 0.01% or more and 0.10% or less

[0039] Al is an element necessary for deoxidation, and to obtain the effect, it is necessary to contain 0.01% or more. However, even if it is contained over 0.10%, the effect is saturated, so it is made 0.10% or less, preferably 0.09% or less.

[0040] N: 0.006% or less

[0041] N forms coarse nitrides and deteriorates the bending crush resistance, so the content needs to be suppressed. When N exceeds 0.006%, this tendency becomes significant, so the N content is set to 0.006% or less. Preferably, it is 0.005% or less. The lower limit of N can be 0%, but from the perspective of manufacturing cost, it is preferably 0.0003% or more.

[0042] Nb: 0.003% or more and 0.018% or less

[0043] Nb is an element that can contribute to the improvement of strength by forming fine carbonitrides, and is an element that refines the austenite grain size during hot pressing and thus contributes to the improvement of delayed fracture resistance. In order to exert such an effect, the Nb content is set to 0.003% or more. Preferably, it is 0.005% or more. On the other hand, even if a large amount of Nb is contained, the above effect is saturated, and the toughness of the steel billet is deteriorated, thereby increasing the manufacturing cost. Therefore, the Nb content is set to 0.018% or less. Preferably, it is 0.016% or less.

[0044] Ti: 0.008% or more and 0.100% or less

[0045] Ti is an element that can contribute to the improvement of strength by forming fine carbonitrides. In particular, fine Ti carbides become strong hydrogen trapping sites, and are therefore very effective for delayed fracture resistance. In order to exert such an effect, the Ti content is set to 0.008% or more. On the other hand, if a large amount of Ti is contained, the elongation after hot pressing is significantly reduced, so the content is set to 0.100% or less. Preferably, it is 0.06% or less.

[0046] B: 0.0005% or more and 0.0050% or less

[0047] B is an element that improves the hardenability during hot pressing and thus contributes to the formation of martensite after hot pressing, i.e., high strength. In addition, it segregates at the grain boundaries, thereby increasing the grain boundary strength, and is therefore effective for delayed fracture resistance. In order to exert this effect, it is contained at 0.0005% or more. However, when contained in excessive amounts, coarse precipitates are generated with N, thereby reducing delayed fracture resistance. Therefore, its content is set to 0.0050% or less. Preferably, it is 0.0035% or less.

[0048] Sb: 0.003% or more and 0.015% or less

[0049] Sb has the effect of suppressing the decarburization layer generated on the surface of the steel plate when the steel plate is exposed to high temperature (from the time when the steel plate is heated before hot pressing to the time when hot pressing is performed). Therefore, the potential distribution on the surface becomes uniform, and the delayed fracture resistance is improved. In addition, by suppressing decarburization, a specified Ti-based carbide can be obtained. In order to show such an effect, its amount is set to 0.003% or more. Preferably, it is 0.004 or more. On the other hand, when Sb exceeds 0.015%, the rolling load increases, which reduces productivity, so it is set to 0.015% or less. It should be noted that it is preferably 0.012% or less.

[0050] 2.0≤Ti / Sb≤20.0

[0051] Ti / Sb affects the precipitation of Ti-based carbides. Here, Ti / Sb refers to the ratio of the content (mass %) of Ti to Sb. When Ti / Sb exceeds 20.0, that is, when the amount of Ti is excessive or the amount of Sb is too little, there is less carbon in the steel, and Ti-based carbides are precipitated from high temperatures. Therefore, the Ti-based carbides are coarsened, and the desired fine Ti-based carbides cannot be obtained. On the other hand, when Ti / Sb is less than 2.0, that is, when the amount of Ti is too little or the amount of Sb is too much, the amount of Ti-based carbides generated decreases. Therefore, in order to generate the specified Ti-based carbides and show the effect of improving the delayed fracture resistance, Ti / Sb is set to be greater than 2.0 and less than 20.0. It should be noted that it is preferably less than 15.0%. More preferably, it is less than 10.0%. The lower limit is preferably greater than 3.0, and more preferably greater than 4.0.

[0052] In the present invention, in addition to the above-mentioned components, one or two or more of the following components may be contained.

[0053] Mo: 0.35% or less

[0054] Mo is an element that improves the hardenability during hot pressing, and thus contributes to the formation of martensite after hot pressing, i.e., high strength. However, even if a large amount of Mo is added, the above effect is saturated, which leads to an increase in cost and deterioration in chemical conversion treatment properties, so it is preferably set to 0.35% or less. When Mo is contained, in order to obtain this effect, it is preferably contained at 0.005% or more. More preferably, it is 0.01% or more.

[0055] Cr: 0.35% or less

[0056] Cr is also an element that improves the hardenability during hot pressing, similar to Mo, and therefore contributes to the formation of martensite after hot pressing, i.e., high strength. However, even if a large amount of Cr is added, the above effect is saturated, and the plating property deteriorates due to the formation of surface oxides, so it is preferably set to 0.35% or less. When Cr is contained, in order to obtain this effect, it is preferably contained at 0.005% or more. More preferably, it is 0.01% or more.

[0057] V: 0.05% or less

[0058] V can contribute to improving strength by forming fine carbonitrides. Due to such effects, it is preferable to contain 0.01% or more of V. On the other hand, when a large amount of V is added, delayed fracture resistance deteriorates, so the content is preferably made 0.05% or less.

[0059] Ca: 0.005% or less

[0060] Ca controls the shape of sulfides and oxides and inhibits the formation of coarse MnS, thereby improving delayed fracture resistance. In order to achieve such an effect, Ca is preferably contained at 0.0005% or more. In addition, excessive addition deteriorates workability, so it is preferably set to 0.005% or less.

[0061] Cu: 0.50% or less

[0062] Cu contributes to high strength through solid solution strengthening, increases hydrogen overvoltage, and thus can improve delayed fracture resistance. In order to exert these effects, it is preferably contained at least 0.002%. On the other hand, even if it contains more than 0.50%, the effect is saturated, and surface defects caused by Cu are easily generated, and delayed fracture resistance is reduced, so its content is preferably set to 0.50% or less.

[0063] Ni: 0.50% or less

[0064] Ni also improves corrosion resistance like Cu, and can reduce the potential difference between the weld and the nut or bolt, so it can improve delayed fracture resistance. In addition, if added together with Cu, it has the effect of suppressing surface defects caused by Cu. In order to exert such an effect, it is preferably contained at least 0.05%. However, when a large amount of Ni is added, the bending crush resistance decreases and the tensile shear stress decreases, so its content is preferably set to 0.50% or less.

[0065] Sn: 0.50% or less

[0066] Sn also improves corrosion resistance like Cu, thus improving delayed fracture resistance, so it can be added as needed. In order to exert these effects, it is preferably contained at least 0.05%. However, when a large amount of Sn is added, the delayed fracture resistance decreases, so its content is preferably set to 0.50% or less.

[0067] The balance other than the above is Fe and inevitable impurities. Examples of inevitable impurities include Zn, Co, Zr, Ta, and W, and the allowable ranges of their contents are Zn: 0.01% or less, Co: 0.10% or less, Zr: 0.10% or less, Ta: 0.10% or less, and W: 0.10% or less.

[0068] Next, the microstructure of the hot pressed component of the present invention will be described in detail.

[0069] In the microstructure of the hot pressed component, the volume fraction of martensite is 95% or more, the average grain size of the prior austenite is 7 μm or less, and the cementite with a grain size of 0.10 μm or more is 2 / μm. 2 The number of Ti-based carbides with a particle size of 0.10 μm or less is 0.20 / μm. 2 It should be noted that the volume fraction described here is a volume fraction relative to the entire steel plate, and the same applies hereinafter.

[0070] When the volume fraction of martensite is less than 95%, the desired tensile strength cannot be obtained. Therefore, the volume fraction of martensite is set to be 95% or more. It should be noted that as the residual structure, ferrite, bainite, pearlite, and retained austenite may be contained, and if they are less than 5%, the effect of the present invention can be exhibited.

[0071] If the average grain size of the prior austenite of the hot pressed component exceeds 7 μm, the delayed fracture resistance property deteriorates. Therefore, the average grain size of the prior austenite is set to 7 μm or less, preferably 6 μm or less.

[0072] The cementite with a particle size of 0.10 μm or more is set to 2 / μm 2 More than 2 pieces / μm2 When the martensite is not tempered sufficiently, fracture occurs before the plasticity is unstable, and thus the tensile strength cannot be obtained. In addition, the structure cannot function as a sufficient hydrogen capture point, and thus the delayed fracture resistance is reduced. The upper limit is not particularly limited, but is preferably 30 / μm. 2 the following.

[0073] Ti-based carbides with a particle size of 0.10 μm or more are set to 0.20 pieces / μm 2 Ti-based carbides with a particle size of 0.10 μm or more are less than 0.20 pieces / μm 2 When the number of hydrogen trapping sites is less than 0.01, the delayed fracture resistance is reduced. The upper limit is not particularly limited, but is preferably 0.90 / μm. 2 the following.

[0074] It should be noted that the microstructure of the hot-pressed component of the present invention can be measured by the method described in the examples described later.

[0075] Next, the plating layer of the hot-pressed component of the present invention will be described in detail.

[0076] The hot pressed component of the present invention may not be coated, but may have a coating on the surface of the hot pressed component to prevent oxidation caused by hot pressing or to improve corrosion resistance. When the hot pressed component has a coating on the surface, the component portion other than the coating has the above-mentioned composition and microstructure.

[0077] In the present invention, the plating layer is preferably an Al-based plating layer or a Zn-based plating layer. By having these plating layers, oxidation of the steel sheet surface caused by hot pressing can be prevented, and the corrosion resistance of the hot pressed component is improved.

[0078] As the Al-based plating layer, for example, an Al-Si plating layer formed by hot-dip plating can be exemplified. In addition, as the Zn-based plating layer, for example, a hot-dip Zn layer formed by hot-dip plating, an alloyed hot-dip Zn layer formed by alloying the hot-dip Zn layer, an electroplated Zn layer formed by electroplating, an electroplated Zn-Ni alloy layer, etc. can be exemplified.

[0079] However, the Al-based coating or Zn-based coating is not limited to the above-mentioned coating, and may be a coating containing one or more of Si, Mg, Ni, Fe, Co, Mn, Sn, Pb, Be, B, P, S, Ti, V, W, Mo, Sb, Cd, Nb, Cr, Sr, etc. in addition to Al or Zn as the main component. There is no limitation on the formation method of the Al-based coating or Zn-based coating, and known hot-dip plating, electroplating, vapor deposition, etc. may be applied. In addition, the Al-based coating or Zn-based coating may be a coating that has been alloyed after the plating process.

[0080] In the present invention, the Zn-based plating layer is more preferably a Zn—Ni alloy plating layer, particularly from the viewpoint of further improving the corrosion resistance of the hot-pressed component and preventing liquid metal brittle cracking caused by molten Zn during hot press forming.

[0081] It should be noted that, if a cold rolled steel sheet before hot pressing to which an Al-based coating or a Zn-based coating is applied is hot pressed, a part or all of the coating components contained in the Al-based coating or the Zn-based coating diffuses into the base steel sheet to generate a solid solution phase and an intermetallic compound, and conversely, Fe as a component of the base steel sheet diffuses into the Al-based coating or the Zn-based coating to generate a solid solution phase and an intermetallic compound. In addition, an oxide film containing Al is generated on the surface of the Al-based coating, and an oxide film containing Zn is generated on the surface of the Zn-based coating.

[0082] If an example is cited, when the Al-Si coating is heated, the coating changes to a coating whose main body is a Fe-Al intermetallic compound containing Si. In addition, when a hot-dip Zn layer, an alloyed hot-dip Zn layer, an electroplated Zn layer, etc. are heated, a FeZn solid solution phase, a ZnFe intermetallic compound, a ZnO layer on the surface, etc., in which Zn is solid-dissolved in Fe, is formed. In addition, when an electroplated Zn-Ni alloy layer is heated, a solid solution layer containing Ni, an intermetallic compound with ZnNi as the main body, a ZnO layer on the surface, etc., in which a coating component is solid-dissolved in Fe, is formed.

[0083] It should be noted that in the present invention, as described above, the Al-containing coating formed by heating a cold-rolled steel sheet before hot pressing to which an Al-based coating is applied is referred to as an Al-based coating, and the Zn-containing coating formed by heating a cold-rolled steel sheet before hot pressing to which a Zn-based coating is applied is referred to as a Zn-based coating.

[0084] The coating weight is not particularly limited and may be a general coating weight. For example, the coating weight per single side is preferably 5 to 150 g / m 2 The coating adhesion is less than 5g / m 2 When the thickness exceeds 150 g / m 2 Sometimes, the plating peeling resistance is deteriorated.

[0085] Next, the method for producing the hot-pressed member of the present invention will be described.

[0086] The cold-rolled steel sheet having the above-mentioned composition (chemical composition) is heated to a temperature range above the Ac3 transformation point and below 1000°C and then hot pressed. After cooling to below Ms point - 200°C, it is reheated under the conditions of a reheating temperature of 100°C to 220°C and a holding time of 1 minute to 40 minutes.

[0087] First, preferred production conditions for a cold-rolled steel sheet before hot pressing will be described.

[0088] [Hot rolling process]

[0089] The smelting method of the steel raw material (steel billet) is not particularly limited, and known smelting methods such as converters, electric furnaces, and vacuum melting furnaces are all suitable. The casting method is also not particularly limited, and the desired size can be manufactured by known casting methods such as continuous casting. It should be noted that there is no problem in applying the ingot casting-blowing rolling method instead of the continuous casting method. The molten steel can also be further subjected to secondary refining such as ladle refining.

[0090] The steel billet as the raw material is preferably reheated after casting and heated at 1250°C or above and 1400°C or below for 80 minutes or more and 180 minutes or less before hot rolling. When the heating temperature is lower than 1250°C or the heating time is less than 80 minutes, the amount of Ti-based precipitates re-solidified is reduced, and coarse Ti-based precipitates remain after hot pressing, so the delayed fracture resistance is reduced. It is more preferably above 1270°C. In addition, when it exceeds 1400°C or the heating time exceeds 180 minutes, the grain size is coarsened, and the desired grain size cannot be obtained after the final annealing, so the delayed fracture resistance is reduced. It is more preferably below 1350°C or less than 150 minutes.

[0091] It should be noted that in the present invention, in addition to the existing method of cooling the steel billet to room temperature and then reheating it after manufacturing, energy-saving processes such as direct rolling, which involves loading the steel billet into a heating furnace in a warm state without cooling, or immediately rolling the steel billet after keeping it warm, or directly rolling the steel billet after casting, can also be applied without any problems.

[0092] Finish rolling end temperature: 850℃ or higher and 950℃ or lower

[0093] In order to improve the delayed fracture resistance after annealing by homogenizing the structure in the steel plate and reducing the anisotropy of the material, the hot rolling needs to be finished in the austenite single phase region, so the finishing temperature of the finishing rolling is preferably set to 850° C. or higher. On the other hand, when the finishing temperature of the finishing rolling exceeds 950° C., the hot rolled structure becomes coarse and the grains after annealing also become coarse, so the upper limit of the finishing temperature of the finishing rolling is preferably set to 950° C.

[0094] Cool down to below 500℃ at an average cooling rate of 80℃ / s or more

[0095] During the cooling process after hot rolling, austenite undergoes ferrite transformation, but ferrite coarsens at high temperatures, so by quenching after hot rolling, the steel sheet structure can be homogenized as much as possible. Furthermore, quenching is performed in order to finely disperse or partially dissolve the Ti carbides. Therefore, it is preferred to cool to below 500°C at an average cooling rate of more than 80°C / second. When the average cooling rate is less than 80°C / second, the ferrite coarsens, so the steel sheet structure of the hot-rolled steel sheet becomes uneven, resulting in a decrease in the delayed fracture resistance after hot pressing. On the other hand, when the cooling stop temperature exceeds 500°C, the Ti carbides in the steel sheet structure of the hot-rolled steel sheet coarsen, so the delayed fracture resistance after hot pressing is reduced.

[0096] Coiling temperature: below 500℃

[0097] When the coiling temperature exceeds 500°C, Ti carbides in the steel sheet structure of the hot-rolled steel sheet coarsen, so the delayed fracture resistance after hot pressing decreases. Therefore, in the present invention, the upper limit of the coiling temperature is preferably set to 500°C. More preferably, it is 450°C or less. It should be noted that there is no particular regulation on the lower limit of the coiling temperature, but if the coiling temperature becomes too low, excessive hard martensite is generated, and the cold rolling load increases, so it is preferably 300°C or more.

[0098] [Pickling process]

[0099] After the hot rolling process, pickling is performed to remove the oxide scale on the surface of the hot rolled sheet. The pickling treatment is not particularly limited and can be performed according to a conventional method.

[0100] [Cold rolling process]

[0101] A cold rolling step is performed to roll the sheet into a cold-rolled sheet having a predetermined thickness. The cold rolling step is not particularly limited and may be performed according to a conventional method.

[0102] [Annealing process]

[0103] In the annealing process, fine ferrite grains are generated by recrystallization after cold rolling. This allows recrystallization to be generated equiaxially and finely during hot pressing, thereby improving tensile strength and delayed fracture resistance. For this reason, it is preferred to heat to a temperature range of 600°C to 700°C at an average heating rate of 5°C / s to 35°C / s, maintain the temperature range of 600°C to 700°C for 30 seconds to 600 seconds, and then cool from the aquifer temperature to room temperature.

[0104] Average heating rate: 5℃ / s or more and 35℃ / s or less

[0105] By controlling the heating rate in the annealing process, the grains after annealing can be refined. If heating is performed quickly, recrystallization is difficult to proceed, so the upper limit of the average heating rate is preferably set to 35°C / second. In addition, when the average heating rate is less than 5°C / second, the grains coarsen, and thus the grain size after hot pressing coarsens, so the lower limit of the average heating rate is set to 5°C / second.

[0106] Soaking temperature: 600°C or higher and 700°C or lower, holding time: 30 seconds or higher and 600 seconds or lower

[0107] The soaking temperature is set to a temperature range higher than the recrystallization temperature. When the soaking temperature is lower than 600°C or the holding time is less than 30 seconds, recrystallization does not proceed sufficiently, so the delayed fracture resistance after hot pressing is reduced. On the other hand, when the soaking temperature exceeds 700°C or the holding time exceeds 600 seconds, Ti-based carbides coarsen. Therefore, it is preferably set to soaking temperature: above 600°C and below 700°C, and holding time: above 30 seconds and below 600 seconds.

[0108] In addition, the cold-rolled steel sheet may be subjected to temper rolling. In this case, the preferred elongation is 0.05% or more and 2.0% or less.

[0109] Then, a plating treatment such as hot-dip galvanizing may be performed, or the cold-rolled steel sheet may be used directly without the plating treatment. The cold-rolled steel sheet for hot pressing of the present invention may be used as a cold-rolled steel sheet manufactured by the above-mentioned manufacturing process, or a plating process for applying an Al-based plating layer or a Zn-based plating layer may be performed according to the purpose.

[0110] The plating process is not limited in any way, and any known hot-dip plating method, electroplating method, vapor deposition method, etc. can be applied. In addition, alloying treatment may be performed after the plating process.

[0111] Next, the manufacturing conditions for hot pressing the obtained cold-rolled steel sheet will be described.

[0112] In the present invention, the cold-rolled steel sheet serving as the raw material is heated to a temperature range above the Ac3 transformation point and below 1000°C, hot pressed, cooled to below Ms point - 200°C, and then reheated under the conditions of a reheating temperature of above 100°C and below 220°C and a holding time of above 1 minute and below 40 minutes.

[0113] First, the above-mentioned cold-rolled steel sheet is heated to a temperature range of more than the Ac3 transformation point and less than 1000°C. When it is lower than the Ac3 transformation point, the austenite fraction decreases, so the martensite fraction after hot pressing is less than 95%, and the tensile strength cannot be ensured. In addition, when it exceeds 1000°C, the grain size becomes excessively coarse, so the delayed fracture resistance decreases. The heating time is not particularly limited, and it is preferably kept for more than 0 seconds and less than 600 seconds. This is because, when it exceeds 600 seconds, the grain size becomes excessively coarse, so the delayed fracture resistance decreases. It should be noted that the heating furnace used during heating is not particularly limited, and an electric furnace, a gas furnace, an electric heating furnace, a far-infrared heating furnace, etc. can be used.

[0114] The Ac3 phase transition point can be calculated using the following formula.

[0115] Ac3 phase transition point (℃) = 881-206C + 53Si-15Mn-20Ni-1Cr-27Cu + 41Mo

[0116] The element symbols in the formula represent the content (mass %) of each element. Elements not contained are calculated as 0.

[0117] The heated steel sheet is transferred to a press machine and hot pressed. The temperature during hot pressing is not particularly limited, but hot pressing is preferably performed in a range of 550°C to 800°C.

[0118] After hot pressing, the steel is cooled to a temperature below Ms point - 200°C. When the temperature exceeds Ms point - 200°C, the martensitic transformation is not completed and the desired volume fraction of the steel sheet structure cannot be ensured. From the viewpoint of ensuring martensite, the cooling reaching temperature is preferably 140°C or less, and more preferably 120°C or less, in addition to being Ms point - 200°C or less.

[0119] The Ms point can be calculated by the following formula.

[0120] Ms point (℃) = 561-474C-33Mn-17Ni-17Cr-21Mo

[0121] The element symbols in the formula represent the content (mass %) of each element. Elements not contained are calculated as 0.

[0122] The cooling rate from the end of hot pressing to the cooling reaching temperature is not limited, but when the cooling rate is too fast compared to 80°C / second, the delayed fracture is reduced due to the deterioration of martensite toughness. On the other hand, when the cooling rate is too slow compared to 20°C / second, it is difficult to ensure strength. Therefore, the cooling rate is preferably 20°C / second or more and 80°C / second or less.

[0123] Next, reheating is performed under the conditions of a reheating temperature of 100°C to 220°C and a holding time of 1 minute to 40 minutes. Reheating after hot pressing coarsens the cementite, so it is an important process in the present invention. The conditions are to implement it for 1 minute to 40 minutes in a temperature range of 100°C to 220°C. When the reheating temperature is lower than 100°C, the amount of dissolved C increases, and the delayed fracture resistance decreases. When the reheating temperature exceeds 220°C, the Ti carbide coarsens, and the delayed fracture resistance cannot be ensured. In addition, when the holding time is less than 1 second, the amount of dissolved C increases, and the delayed fracture resistance decreases. When the holding time exceeds 40 minutes, the Ti carbide coarsens, and the delayed fracture resistance cannot be ensured.

[0124] As described above, the hot-pressed component of the present invention can be obtained.

[0125] Example

[0126] It should be noted that the present invention is not limited to the following embodiments, but can be implemented with appropriate modifications within the scope of the present invention, and all of these are included in the technical scope of the present invention.

[0127] Steel having the component composition shown in Table 1 was melted, and formed into a steel slab by continuous casting, and then hot rolled at the heating temperature and the finishing temperature (FDT) shown in Table 2. Then, the obtained hot rolled steel sheet was cooled to the cooling stop temperature at the average cooling rate shown in Table 2, cooled to the coiling temperature (CT), and coiled into a coil.

[0128] Next, the obtained hot-rolled sheet was pickled and then cold-rolled to obtain a cold-rolled sheet (sheet thickness: 1.4 mm).

[0129] The cold-rolled steel sheets thus obtained were annealed in a continuous annealing line (CAL) or a continuous hot-dip coating line (CGL) under the conditions shown in Table 2, and the steel sheets that passed the continuous annealing line (CAL) obtained cold-rolled steel sheets (CR). In addition, hot-dip galvanized steel sheets (GI) and hot-dip aluminum steel sheets (AS) were obtained for the steel sheets that passed the CGL. It should be noted that, for a portion of the steel sheets that passed the CGL, after hot-dip galvanizing, alloying treatment was further performed at 550°C to obtain alloyed hot-dip galvanized steel sheets (GA). In addition, after a portion was annealed using CAL, an electro-galvanized nickel steel sheet (EZN) was obtained in an electro-galvanizing line (EGL).

[0130] Next, the obtained cold-rolled steel sheet (including the plated steel sheet) is subjected to hot pressing.

[0131] The die used in the hot press is a punch width of 70 mm, a punch shoulder of R4 mm, a die shoulder of R4 mm, and a forming depth of 30 mm. The cold-rolled steel sheet is heated in the atmosphere using either an infrared heating furnace or an atmosphere heating furnace depending on the heating rate. In addition, the cooling after pressing is a combination of sandwiching the steel sheet between the punch and the die and air cooling on the die opened from the sandwiching, and cooling from the pressing (starting) temperature to room temperature.

[0132] A JIS No. 5 tensile test piece was cut out from the bottom of the cap of the hot-pressed member thus obtained, and a tensile test was performed in accordance with JIS Z2241 to measure the tensile strength (TS).

[0133] In addition, for the test of delayed fracture resistance, a JIS No. 5 tensile test piece was cut from the bottom of the cap of the hot press component and a constant load test was performed. A load was applied while immersing in a solution of hydrochloric acid with a pH of 3 at room temperature to evaluate the presence or absence of fracture. The load stress was set to 800 MPa, and the delayed fracture resistance was set to good (○) if there was no fracture for more than 100 hours, and the delayed fracture resistance was set to poor (×) if fracture occurred in less than 100 hours.

[0134] Regarding the volume fraction of martensite in the hot-pressed component, a sample was cut from the hot-pressed component in such a manner that a cross section parallel to the rolling direction of the cold-rolled steel sheet before hot pressing and parallel to the thickness direction was used as an observation surface. The observation surface was polished and then corroded with a 3 volume % nitric acid ethanol solution. The sample was observed using a SEM (scanning electron microscope) at a magnification of 5000 times, and the area ratio was measured by a point counting method (according to ASTM E562-83 (1988)), and the area ratio was used as the volume fraction.

[0135] The average crystal grain size of the prior austenite in the hot-pressed component is obtained as follows. A sample is cut from the hot-pressed component in a manner that the cross section parallel to the rolling direction of the cold-rolled steel sheet before hot pressing and parallel to the thickness direction is the observation surface, the observation surface is polished, and then etched with a 3 volume % nitric acid ethanol solution, and observed using a SEM (scanning electron microscope) at a magnification of 3000 times, and the equivalent circle diameter of the prior austenite grain is calculated using Image-Pro of Media Cybernetics, and these values ​​are averaged to obtain the average.

[0136] The particle size of cementite was observed by using a TEM (transmission electron microscope) at a magnification of 15,000 times. Using Image-Pro, the lower limit was set to 0.005 μm, and its equivalent circle diameter was calculated to obtain the particle size. The number of cementite particles with a particle size of 0.10 μm or more was converted to 1 μm. 2The number of cementites existing in the embodiment of the present invention is determined as the average value of 20 arbitrary locations, and the average value is defined as the number of cementites having a grain size of 0.10 μm or more.

[0137] The particle size of Ti-based carbides was observed by TEM at a magnification of 20,000 times. Using Image-Pro, the lower limit was set to 0.005 μm, and the equivalent circle diameter was calculated to obtain the particle size. The number of Ti-based carbides with a particle size of 0.10 μm or less was converted to 1 μm. 2 The number of cementites existing in the embodiment of the present invention is determined as the average value of 20 arbitrary locations, and the average value is defined as the number of cementites having a grain size of 0.10 μm or more.

[0138] The results are shown in Table 3.

[0139]

[0140]

[0141] [Table 3]

[0142]

[0143] ※Underlined words are outside the scope of the invention

[0144] From the results in Table 3, it can be seen that all the examples of the present invention have both a tensile strength of 2100 MPa or more and excellent delayed fracture resistance.

Claims

1. A hot pressed component, comprising, by mass%, C: 0.42% to 0.53%, Si: 0.01% to 0.80%, Mn: 1.0% to 2.0%, P: 0.03% to 0.10%, S: 0.003%, Al: 0.01% to 0.10%, N: 0.006% to 0.003%, Nb: 0.003% to 0.018%, Ti: 0.008% to 0.100%, B: 0.0005% to 0.0050%, Sb: 0.003% to 0.015%, the balance being Fe and unavoidable impurities, satisfying 2.0≤Ti / Sb≤20.0, The microstructure is as follows: the volume fraction of martensite is 95% or more, the average grain size of the prior austenite is 7 μm or less, and the cementite with a grain size of 0.10 μm or more is 2 / μm. 2 The number of Ti-based carbides with a particle size of 0.10 μm or less is 0.20 / μm. 2 above, The tensile strength of the hot-pressed component is greater than 2100 MPa.

2. The hot-pressed component according to claim 1, wherein: As a component composition, it further contains, in mass %, one or more selected from Mo: 0.35% or less, Cr: 0.35% or less, V: 0.05% or less, Ca: 0.005% or less, Cu: 0.50% or less, Ni: 0.50% or less, and Sn: 0.50% or less.

3. The hot-pressed component according to claim 1 or claim 2, wherein: The hot-pressed member has an Al-based plating layer or a Zn-based plating layer on its surface.

4. A method for manufacturing a hot-pressed component, wherein: A cold-rolled steel sheet having a component composition as described in claim 1 or claim 2 is heated to a temperature range above the Ac3 transformation point and below 1000°C and then hot pressed, cooled to below Ms point - 200°C, and then reheated under the conditions of a reheating temperature of 100°C to 220°C and a holding time of 1 minute to 40 minutes.

Citation Information

Patent Citations

  • Edible fat composition

    JP1984042841A

  • Steel and concrete synthetic durable wall

    JP1985062352A

  • Hot-pressed steel sheet member and method for producing same

    CN111344425A

  • Hot-pressed member and method for manufacturing same, and cold-rolled steel sheet for hot pressing and method for manufacturing same

    US20200131596A1